KAJIAN KONSEP EKOWISATA BERBASIS MASYARAKAT DALAM MENUNJANG PENGEMBANGAN PARIWISATA: SEBUAH STUDI LITERATUR - Rifqi Asy’ari; Reiza D. Dienaputra; Awaludin Nugraha; Rusdin Tahir; Cecep Ucu Rakhman; Rifki Rahmanda Putra (UHN IGB Sugriwa Denpasar, 2021)
Along with the development of the era, the terminology of ecotourism has continued to develop without eliminating the essential in the definition of ecotourism itself, namely conservation or conservation for nature, culture and society itself. The concept of community-based ecotourism became a concept that developed in the 2000s where the terminology of this concept is more appropriate to involve the community in planning, implementing ecotourism management and all the benefits that are obtained. This study examines the extent to which the concept of community-based ecotourism supports tourism development and what are the obstacles in the concept of community-based ecotourism which can then become recommendations for further research. The method used is a qualitative method in the form of a literature study of the 20 articles obtained. The search tool used is to analyze or dismantle, then the data is analyzed using the literature review method with traditional review techniques. The concept of community-based ecotourism in the context of tourism development can be interpreted as a form of development in resource use by involving the community as the key holder. The concept of community-based ecotourism is also a new concept and opens up opportunities to enrich the study. The indicators obtained from the analysis show that the indicators of resources, community and tourists are factors in tourism development using the concept of community-based ecotourism.